Assessment of Pepper Pungency Using Real Time PCR to Evaluate the Pun1 AND Catf2 Genes Expression in Capsicum Annuum Varieties of Takanotsume Hot Pepper and Yellow Bell Pepper - Tiwari, Shishir; Sao, Shweta; Kurrey, Antu (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The accumulation of the alkaloid capsaicin and its derivatives in Capsicum fruits results in their pungent flavor. A RT-PCR assay was used to examine the pungency levels of Capsicum annuum species by employing gene-specific primers associated with the capsaicin biosynthetic pathway. The expression of the Acyl-transferase encoded by the Pun1 and Catf2 was directly related to capsaicin accumulation. Low-abundance mRNA transcripts were measured with RT-PCR. Pun1 and Catf2 gene expression was found to be correlated with the phenotypic trait (pungency level) in our study, and has a useful method for distinguishing between Capsicum species' pungency levels. The RT-PCR results showed that the candidate capsaicin biosynthetic genes (Pun1, and Catf2) were present in Capsicum annuum species with high and moderate levels of pungency, whereas the expression levels of these two genes were low in yellow bell pepper (Non-Pungent) with low levels of pungency and high expression level was measured in Takanotsume Hot Pepper variety. In conclusion, gene specific PCR data, gene expression profile and volatile compounds analysis collectively indicate that the Pun1 and Catf2 genes in pepper encodes a acyltransferase. The Pun1 and Catf2 genes in pepper had crucial role in pungency level of peppers.